The Critique and Examination of the Book: Islamic Thought 1 - Morteza Shajari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Islamic Thought 1 is a book which has been written for bachelor students of all fields, and it has reached its 97th edition. The book seeks to examine three important doctrinal principles, including human, God, and resurrection. But unfortunately the book has not utilized great Islamic intellectuals’ opinions, namely Avicenna, Abu Hamid al-Gazali, Sheikh Ishraq, and Mulla Sadra. The authors of this book have presented their own accepted opinions with theological attitudes and with very weak reasons. When they realized the weaknesses of traditional theology reasoning, and and when they could not provide rational  proofs for it, they drew on some terms  and reasoning of transcendental wisdom, which per se led to some contradictions in represented opinions in this book. The author of this paper believes that this book does not represent any thoughts, nor does it reflectany Islam of great intellectuals like Mulla-Sadra